2019
DOI: 10.3390/app9132767
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Tyrosyl-DNA Phosphodiesterase 1 Inhibitors. Combination of Monoterpene and Adamantine Moieties via Amide or Thioamide Bridges

Abstract: Eleven amide and thioamide derivatives with monoterpene and adamantine substituents were synthesised. They were tested for their activity against the tyrosyl-DNA phosphodiesterase 1 DNA (Tdp1) repair enzyme with the most potent compound 47a, having an IC50 value of 0.64 M. When tested in the A-549 lung adenocarcinoma cell line, no or very limited cytotoxic effect was observed for the ligands. However, in conjunction with topotecan, a well-established Topoisomerase 1 (Top1) poison in clinical use against cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…In addition to the activity assay that we reported above, we wanted to confirm the interactions between compound 3ba and Tdp1 before progressing to in vivo studies. Using an intrinsic tryptophan fluorescence quenching assay that we previously applied to study the binding interactions of Tdp1 and its inhibitors [43,45,48,49,52], we evaluated the binding of compound 3ba to recombinant Tdp1. Clear quenching of the Tdp1 intrinsic fluorescence was observed upon the addition of 3ba (Supplementary Figure S1).…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the activity assay that we reported above, we wanted to confirm the interactions between compound 3ba and Tdp1 before progressing to in vivo studies. Using an intrinsic tryptophan fluorescence quenching assay that we previously applied to study the binding interactions of Tdp1 and its inhibitors [43,45,48,49,52], we evaluated the binding of compound 3ba to recombinant Tdp1. Clear quenching of the Tdp1 intrinsic fluorescence was observed upon the addition of 3ba (Supplementary Figure S1).…”
Section: Biologymentioning
confidence: 99%
“…To date, many Tdp1 inhibitors have been identified. A major class of Tdp1 inhibitors comprises those based on natural products including usnic acid derivatives [41][42][43][44][45], coumarins [46], adamantanes [47][48][49], nucleoside analogs [50], dehydroabietylamine derivatives [51], chromenes [52], bile acids derivatives [53], and fungal products [54][55][56]. There are also early reports of Tdp1 inhibition based on diamidines [57], antibiotics [58,59], steroids [60], and other compounds [61].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these derivatives exhibit analgesic, antiviral, neuroprotective, and antitumor properties [ 14 ]. Moreover, new classes of TDP1 inhibitors with submicromolar half maximal inhibitory concentration (IC 50 ) values have been developed that contain monoterpene moieties; for example, coumarin [ 16 ], 4-arylcoumarin [ 17 ], and adamantane [ 18 , 19 , 20 , 21 ] derivatives as well as octahydro-2 H -chromenes 3 (see Figure 1 ) synthesized from p -menthane monoterpenoid (-)-isopulegol [ 22 ]. Their ability to enhance the Tpc cytotoxic potential was demonstrated for several of these derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 7-hydroxycoumarin derivative 4 ( Figure 1 ) with a pinene-type fragment reduced the CC 50 (median cytotoxic concentration causing 50% cell death) of camptothecin eight-fold for the human breast adenocarcinoma cell line MCF-7 [ 16 ] while the hybrid molecule 5 , comprising of (4-fluorophenyl)-coumarin and geraniol moieties, showed a significant increase in the antitumor effect of Tpc on Krebs-2 ascites in an in vivo tumor model [ 17 ]. Among the adamantane derivatives, strong synergism was found for 6 and 7 ( Figure 1 ), both containing the acyclic monoterpene substituents, when lung adenocarcinoma cells A549 were treated in combination with Tpc [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tdp1 inhibitors have also been found from natural sources. It has been reported that natural products that are isolated from anamorphic fungus (e.g., compound 5 , Figure 2) [12], triptamine derivatives of bile acids 6 [13], and monoterpenoid derivatives such as 7 and 8 that are attached to 7-hydroxycoumarin [14] or adamantane fragments [15,16,17] all show inhibitory activity against Tdp1 in the micromolar and submicromolar concentration ranges.…”
Section: Introductionmentioning
confidence: 99%